REFORMULATION OF FAMILY LEGAL IN INDONESIA FOR FEMALE MASLAHAH - Wahidullah Wahidullah; Murniati Murniati; Yushinta Eka Farida; Jumaiyah Jumaiyah (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: One form of innovation proposed by Islamic banks to support the needs of the community is The Sharia Gold-pawning Service. However, worries arise for the Rahn service (gold pawning) since the service is not beneficial in gaining profits. By this service, Islamic banks only gain profits from the maintenance service of goods that are pledged as collateral. The problem occurs as the profit is taken from the percentage of the amount of the loan provided by a Sharia bank to its customer which is considered to have no cost differential as the practices undertaken in conventional banking. Therefore, this is an interesting topic to discuss among academics related to the amount and calculation of maintenance services that customers must pay to the bank. If maintenance services are determined based on the percentage of the financing or loan’s amount, then there is a credit interest value on the financing that must be returned by the customer as a collateral for maintenance services calculated from the amount of the loan. Thus, this study is intended to analyze the concept of covenant and its application in financing gold pawning in Islamic banks. The objects of this study are those concerning the Islamic Commercial Bank, including Bank Syariah Mandiri and Bank Jabar Banten Syariah.Abstrak: Di dalam Undang-undang Nomor 1 tahun 1974 Pasal 3 ayat 1 dan 2, memberikan penjelasan tentang asas perkawinan adalah monogami akan tetapi bersifat terbuka, atau dalam KHI menggunakan istilah poligami terbatas sampai dengan empat isteri, akan tetapi dengan catatan kemampuan memberi nafkah dan berbuat adil terhadap isteri-isteri dan anak-anaknya. Rumah tangga yang dibangun berdasarkan poligami sebagian masyarakat menjadi hal yang kontroversi, akan tetapi normatifitas hukum telah disahkan dan itu sebuah realitas sosial terjadi. Metode yang digunakan dalam penelitian ini dengan mengumpulkan data berupa pustaka pustaka (literature research), adapun langkah-langkah dalam penelitian ini dengan membaca literatur berupa buku, artikel, peraturan perundang-undangan serta fatwa. Data tersebut di analisis dengan metode deskriftif kualitatif guna memperoleh hasil penelitian dengan berpijak pada teori yang terkait dengan penelitian Hasil penelitian menunjukan bahwa tidak ada perempuan yang rela di poligami. Pada kasus poligami perempuan merupakan obyek kekerasan yang terbungkus rapi dalam kehidupan rumahtangga.